Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Kantor Kecamatan Pamulang - Chairunnida Azzahra; Neneng Tita Amalya (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study was to determine the effect of Discipline and Motivation variables both partially and simultaneously on Employee Performance at the Pamulang District Office with a sample of 52 people. The method used is a quantitative method. Data analysis used in this study is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and F test. The results of this study are Price has a significant effect on Employee Performance on the regression Y = 18.294 + 0.503X1, the correlation value is 0.577 meaning that the two variables have a moderate level of relationship. Motivation has a significant effect on Employee Performance with the regression equation Y = 6.088 + 0.646X2 the correlation value is 0.646 meaning that the two variables have a strong level of relationship. Discipline and Motivation simultaneously have a significant effect on Employee Performance with the regression equation Y = 12.332 + 0.112X1 + 0.554X2. The coefficient of determination value is 48%, while the remaining 52% is caused by other variables not examined in this study. The results of testing the first hypothesis obtained a calculated t value> t table or (4.993)> t_table (1.675). Based on the results of testing the second hypothesis, the calculated t value> t table or (6.706)> t_table (1.675) was obtained. Based on the results of testing the third hypothesis, the calculated F value> f table (22.655> 3.10) was obtained. This shows that simultaneously the variables Discipline and Motivation have a significant influence on Employee Performance.